Change in hematology prepartum and postpartum of Garut ewe fed with flushing diet contain lemuru oil - A., Nurlatifah; L., Khotijah; R I., Arifiantini; M. S., Maidin; D. A., Astuti (IOP Publishing, 2022)
Nutrients play a vital role in the sustainability of sheep production by maintaining the reproductive process and the health status of the ewe. This study evaluated blood hematology changes during prepartum and postpartum on ewe fed flushing diet. A total of 20 Garut sheep were used in this study. A completely randomized factorial design 4 × 2 was used. The first factor was ration (P1= basal ration; P2= Flushing concentrate 6% palm oil; P3= Flushing concentrate 3% palm oil and 3% lemuru oil; P4= Flushing concentrate 6% lemuru oil), and the second factor was a physiological phase (prepartum and postpartum ). Erythrocyte and hemoglobin levels were higher postpartum than in the prepartum period (P<0,05), but the ration was not affected. The postpartum ewe has a lower percentage of lymphocyte and monocyte but higher neutrophil than the prepartum period. P2, P3, and P4 significantly (P<0,05) improved the number of monocytes. P3 significantly (P<0,05) decrease lymphocyte and increase neutrophil. The neutrophil to lymphocyte (N/L) ratio is very low in P4 and high in P3. In conclusion, feeding flushing concentrate 6% lemuru oil can improve the immune system by maintaining normal blood hematology during the prepartum and postpartum.